Advances of Fibroblast Growth Factor/Receptor Signaling Pathway in Hepatocellular Carcinoma and its Pharmacotherapeutic Targets - Wang, Haijun; Yang, Jie; Zhang, Ke; Liu, Jia; Li, Yushan; Su, Wei; Song, Na (Frontiers in Pharmacology, 2021)
Hepatocellular carcinoma (HCC) is a type of primary liver cancer with poor prognosis, and its incidence and mortality rate are increasing worldwide. It is refractory to conventional chemotherapy and radiotherapy owing to its high tumor heterogeneity. Accumulated genetic alterations and aberrant cell signaling pathway have been characterized in HCC. The fibroblast growth factor (FGF) family and their receptors (FGFRs) are involved in diverse biological activities, including embryonic development, proliferation, differentiation, survival, angiogenesis, and migration, etc. Data mining results of The Cancer Genome Atlas demonstrate high levels of FGF and/or FGFR expression in HCC tumors compared with normal tissues. Moreover, substantial evidence indicates that the FGF/FGFR signaling axis plays an important role in various mechanisms that contribute to HCC development. At present, several inhibitors targeting FGF/FGFR, such as multikinase inhibitors, specific FGFR4 inhibitors, and FGF ligand traps, exhibit antitumor activity in preclinical or early development phases in HCC. In this review, we summarize the research progress regarding the molecular implications of FGF/FGFR-mediated signaling and the development of FGFR-targeted therapeutics in hepatocarcinogenesis.